Spontaneous Cooling Enables High‐Quality Perovskite Wafers for High‐Sensitivity X‐Ray Detectors with a Low‐Detection Limit - Wenyi Wu; Jianqiang Zhang; Ciyu Liu; Jiankai Zhang; Hoajie Lai; Zhongqiang Hu; Hai Zhou (Advanced Science)
Abstract Developing high‐quality perovskite wafers is essential for integrating perovskite technology throughout the chip industry chain. In this article, a spontaneous cooling strategy with a hot‐pressing technique is presented to develop high‐purity, wafer‐scale, pinhole‐free perovskite wafers with a reflective surface. This method can be extended to a variety of perovskite wafers, including organic–inorganic, 2D, and lead‐free perovskites. Besides, the size of the wafer with diameters of 10, 15, and 20 mm can be tailored by changing the mold. Furthermore, the mechanism of spontaneous cooling for improving the quality of perovskite wafers is revealed. Finally, the high‐quality lead‐free Cs3Cu2I5 perovskite wafers demonstrate excellent X‐ray detection performances with a high sensitivity of 3433.6 µC Gyair−1 cm−2 and a low detection limit of 33.17 nGyair s−1. Moreover, the Cs3Cu2I5 wafers exhibit outstanding environmental and operational stability even without encapsulation. These research presents a spontaneous cooling strategy to achieve wafer‐scale, high‐quality perovskites with mirror‐like surfaces for X‐ray detection, paving the way for integrating perovskites into electronic and optoelectronic devices and promoting the practical application of perovskite X‐ray detectors.